Enhancement on mechanical strength of adhesively-bonded composite lap joints at cryogenic environment using coiled carbon nanotubes. (1st February 2017) - Ma, Hei-Lam; Jia, Zhemin; Lau, Kin-tak; Li, Xiaofeng; Hui, David; Shi, San-qiang
Abstract: The hardness, tensile and lap joint shear behaviors of pure epoxy, straight multi-walled carbon nanotube (MWNT)/epoxy and coiled multi-walled carbon nanotube (CCNT)/epoxy adhesives conditioned at room temperature (RT) and cryogenic temperature (CT) were investigated in the present study. Experimental results showed that all adhesives had greater Vickers hardness values, Young's moduli and tensile strengths at CT. The performance of CCNT/epoxy adhesive at CT was outstanding due to the enhancement of mechanical interlocking effect between CCNTs and epoxy at low temperature. This effect led to a greater Vickers hardness value, Young's modulus and lap joint shear strength of this adhesive at CT when compared with MWNT/epoxy type. The result from finite element analysis (FEA) also proved that the contraction of matrix at CT induced additional clamping force onto the surface of nanotubes. Due to the larger surface area of CCNTs, a relatively stronger bonding strength was achieved, and thus, CCNT/epoxy adhesive had better mechanical properties at low temperature condition.